Survey on the Difficulties of Learning Arabic and Ways to Overcome Them Among First-Year Students Who Are Not Majors in It at The Centre for Languages and Pre-University Academic Development (CELPAD) At the International Islamic University Malaysia - Zakaria, Ahmad Lutfi; Mohd Zulqurnain, Ajwad; Abu Bakar, Radhwa (Al-Ḍād Journal, 2025)
This research aims to identify the difficulties of learning Arabic and provide suggestions for ways to overcome them among first-year non-specialized students at the Centre for Languages and Pre-University Academic Development (CELPAD) at the International Islamic University Malaysia. This goal was achieved by adopting a comprehensive research methodology that included designing an integrated questionnaire, which was distributed to a sample of students. The extracted data were analysed using the Statistical Package for Social Sciences (SPSS) to ensure the accuracy and reliability of the results, by calculating the percentage, arithmetic mean, and Cronbach's alpha value to assess the level of reliability. The results then showed that the most prominent challenges facing students lie in the prevailing feeling and belief that Arabic is a difficult language to learn. On the other hand, it was found that students prefer to use translation tools as a primary means of understanding Arabic texts, which indicates the need for educational strategies that support this approach and help alleviate the difficulties they face. Keywords: Difficulties, Ways to Overcome, Learning, Non-specialists, Arabic Language.